Familial Predisposition of Primary Dysmenorrhea among Senior High School Girl Students - Prema Sharlini; Hadyana Sukandar; Ryadi Fadil (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Dysmenorrhea is a common female reproductive problem in women of active reproductive agewhich is characterized by menstrual pain or cramps in a women’s lower abdomen or back. Dysmenorrhea can be classified into primary and secondary. One of the associated risk factor of primary dysmenorrhoeais the family history, however the study on the family history of primary dysmenorrhea with recurrent menstrual pain is limited. This study was conducted to identify the correlation between family history and primary dysmenorrhea in high school girls.Methods: This cross sectional study was conducted at several senior high schools in Jatinangor from April−June 2013. One hundred and sixty two students were included in this study. The sample size was calculated based on the unpaired−dichotomous variable for the two−sided formula. A self administered questionnaire was distributed to the senior high school girl students who were in their menarche age, menstrual cycle characteristics, presence or absence of dysmenorrhea, severity of pain and presence dysmenorrhea in mothers and in sisters were inquired. Data were analyzed using chi square test.Results: Overall, there were association between positive family history and primary dysmenorrhea among the students with (p<0.001). The prevalence of dysmenorrhea in the students was 92.6% with 95% confidence interval which was 87.5−95.7%. The prevalence rate was 67.9% in mothers with 95% confidence interval which is 60.4−74.6% and 80.2% prevalence of primary dysmenorrhoea in sisters with 95% confidence interval which is 73.4−85.6%.Conclusions: There is a significant association between positive family history and primary dysmenorrhea.[AMJ.2015;2(4):579–83] DOI: 10.15850/amj.v2n4.643